Antifatigue effect of functional cookies fortified with mushroom powder (Tricholoma Matsutake) in mice. Issue 12 (6th November 2020) - Ma, Ning; Tao, Hongling; Du, Hengjun; Zhao, Liyan; Hu, Qiuhui; Xiao, Hang
Abstract : Abstract: Bakery products made by cereal and edible fungi powder have a unique flavor and health benefits, dramatically enhancing the nutritional value of the products. In this study, we investigated the antifatigue effect of a novel Tricholoma matsutake cookie (TMC) by the exhaustive swimming test. Male Kunming ICR mice were randomly divided into seven groups (each group, n = 10), fed with saline, ordinary cookies (4, 8, 16 g/kg B.W./day), and TMC (4, 8, 16 g/kg B.W./day) by gavage. After 30‐day administration, the weight‐loaded swimming test was carried out on the mice to evaluate the antifatigue effect of TMC. In comparison with the effect of ordinary cookies, the intake of TMC significantly prolonged the exhaustive swimming time of mice and increased the level of muscle glycogen and liver glycogen, accompanied by the reduction of lactic acid and urea nitrogen level in serum. Additionally, TMC dramatically improved the activity of superoxide dismutase and glutathione peroxidase in serum and largely decreased the level of malondialdehyde. All in all, TMC could enforce exhaustive swimming tolerance, accelerate the decomposition of sports‐related metabolites such as lactic acid and urea nitrogen, and increase the activity of the antioxidant enzyme, thereby improving sports‐related energy storage and relieving fatigue. Our findings broadened the application of T. matsutake in the processing of bakery products and provided the theoretical basis and technical support for the development of antifatigue products. Practical Application: In this study, we investigated the antifatigue effect of a novel Tricholoma matsutake cookie by the exhaustive swimming test. Collectively, the results of the present study suggested that the cookies fortified with T. matsutake could be considered as an antifatigue bakery product. Furthermore, our findings broadened the application of T. matsutake in the processing of bakery products and provided the theoretical basis and technical support for the development of antifatigue products.